1984
DOI: 10.1148/radiology.153.2.6484182
|View full text |Cite
|
Sign up to set email alerts
|

The superior sinus of the pericardium: CT appearance.

Abstract: On computed tomography, a mass-like density is often observed, just posterior to the ascending aorta, that occasionally has been mistaken for mediastinal lymph node enlargement. Cadaver studies confirmed this retroaortic structure to be an extension of the pericardial cavity, the superior sinus. Current anatomic texts sometimes depict this space without description. Anatomic studies revealed the presence of a superior sinus in all of the 28 cadavers studied. The mean cross-sectional diameter of the sinus in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In 1 5% of patients this structure may be large enough to simulate an enlarged mediastinal lymph node. Cadaver injections and dissections have shown that this density corresponds to the superior recess of the pericardium, a posterior extension of the pericardial cavity around the ascending aorta [16]. This recess also can be encountered as a normal finding on magnetic resonance imaging of the mediastinum ( fig.…”
Section: Superior Pulmonary Veinsmentioning
confidence: 92%
“…In 1 5% of patients this structure may be large enough to simulate an enlarged mediastinal lymph node. Cadaver injections and dissections have shown that this density corresponds to the superior recess of the pericardium, a posterior extension of the pericardial cavity around the ascending aorta [16]. This recess also can be encountered as a normal finding on magnetic resonance imaging of the mediastinum ( fig.…”
Section: Superior Pulmonary Veinsmentioning
confidence: 92%
“…Current atlases depict these recesses but do not name them [3,6,7]. Only recently has the retroaortic recess been recognized on CT, when it was seen on 49% of CT scans [1]. In our series, the retroaortic recess was shown on only one of four CT scans but on at least 67% of transverse MR scans.…”
Section: Discussionmentioning
confidence: 53%
“…On CT scans, the retroaortic recess has been mistaken for adenopathy [1], and the preaortic recess could be confused with thymic enlargement or anterior mediastinal adenopathy [2], but the low signal intensity of these recesses on MRI permits their differentiation from the slightly higher signal intensity of lymph nodes or thymus.…”
Section: Discussionmentioning
confidence: 99%
“…3A). A similar problem can occur with the superior pencardial recess [2,7]. Continuity of the retroaortic segment with the superior pericardial recess and its visualization at a site only 1 -2 cm to the right of the mid-sagittal plane help in its identification.…”
Section: Discussionmentioning
confidence: 93%